A participação feminina nas aulas de educação física do ensino fundamental II em Miracema do Tocantins-TO - Silva, Maicon Pinto da (Universidade Federal do Tocantins, 2023)
Over the yerars, aswomen have gained their place insociety, however, there are still a number of prejudices related to women, whether in the job market, sports or even the same education, in this sense or in the presente work that had as its main purpose. The objective is to understand what are the mechanisms of inclusion of elementar school students are presente during the Physical Education classes. A reserach carried out had a qualitative character and had questions and answers to reach the proposed objective and verify them, but there is still little visibility for girls in Physical Education classes, thus, the more active children of the classes than the students. It is therefore necessary to include mechanisms for both to participate equally in the classes.